Attentional, interpretation and memory biases for sensory-pain words in individuals with chronic headache. Issue 1 (February 2019) - Schoth, Daniel E; Beaney, Rebecca; Broadbent, Philippa; Zhang, Jin; Liossi, Christina
Introduction: Cognitive biases in attention, interpretation and less consistently memory have been observed in individuals with chronic pain and play a critical role in the onset and maintenance of chronic pain. Despite operating in combination cognitive biases are typically explored in isolation. Aim: The primary aim of this study was to explore attentional, interpretation and memory biases and their interrelationship in individuals with chronic headache. Methods: Twenty-eight participants with chronic headache and 34 healthy controls completed paradigms assessing attentional, interpretation and memory biases with ambiguous sensory-pain and neutral words. Results: Individuals with chronic pain showed significantly greater pain-related attentional and interpretation biases relative to controls, with no differences in memory bias. No significant correlation was found between any of the three forms of cognitive bias assessed. Discussion and conclusion: The clinical implications of cognitive biases in individuals with chronic pain remain to be fully explored, although one avenue for future research would be specific investigation of the implications of biased interpretations considering the consistency of results found across the literature for this form of bias.